Preparation method of atomic-scale clean single-layer graphene transmission electron microscope grid
Through ozone-UV treatment and acetone cleaning, combined with binder and TEM microgate bonding and oxidative etching, the pollution and defect problems in the transfer of single-layer graphene are solved, and lossless transfer and high-resolution TEM imaging of high-quality graphene are achieved.
Patent Information
- Application Number
- CN202510423227.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2025-08-26
AI Technical Summary
In the prior art, single-layer graphene prepared by chemical vapor deposition is prone to cracks, tear or organic matter residues during the transfer process, resulting in a decrease in imaging resolution of transmission electron microscopy and affecting the imaging contrast of light elements and organic small molecules.
The combination of ozone-ultraviolet treatment and acetone cleaning was used to remove organic matter and PMMA residues on the surface of graphene. Then, the binder was used to bond with the TEM microgate, and the metal substrate was removed by an oxidizing etching solution. Finally, the binder and impurities were removed by step-wise heating and pyrolysis in vacuum.
The high-quality single-layer graphene is achieved without damage transfer, which significantly improves the TEM imaging resolution, avoids contamination and structural damage in traditional transfer methods, and is suitable for high-resolution electron microscopy imaging.
Smart Images

Figure CN120545155A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of transmission electron microscopes, and in particular relates to a process for preparing an atomic-level clean single-layer graphene transmission electron microscope (TEM) grid. Background Art
[0002] Graphene is a two-dimensional planar material with a thickness of one atom formed by the hexagonal arrangement of carbon atoms. Single-layer graphene prepared by chemical vapor deposition (CVD) is very popular due to its large-area uniformity and near-intrinsic electrical properties (carrier mobility > 4000 cm 2 / (V·s)), has become an ideal support substrate for transmission electron microscopy characterization of two-dimensional materials and nanodevices. Especially in atomic resolution imaging (such as HRTEM, HRSTEM), the ultra-low background noise (carbon signal intensity is only 1 / 50 of that of traditional amorphous carbon films) and zero contrast interference characteristics of single-layer graphene can significantly improve the imaging contrast of light elements (such as Li, B) and small organic molecules and single-atom clusters. However, the core prerequisite for achieving this technical advantage is: to transfer the graphene prepared by CVD from the growth substrate to the TEM microgrid without damage or contamination, and to ensure its atomic-level cleanliness and strong bonding with the microgrid interface. However, due to the traditional transfer method, graphene may produce cracks, tears or other defects due to mechanical stress or chemical reactions, as well as the resolution limitation of imaging artifacts caused by organic residues, which has hindered the characterization of light elements and organic molecular structures on single-layer graphene by transmission electron microscopy (TEM).
[0003] Currently, commonly used graphene transfer methods include dry transfer and wet transfer. Dry transfer may cause graphene cracking or defects due to mechanical stress. Although wet transfer is relatively simple to operate, it is easy to introduce moisture and solvent residues, leading to graphene surface contamination. Among them, polymer-assisted transfer methods (such as polymethyl methacrylate and polydimethylsiloxane) can maintain the integrity of the graphene structure, but subnanometer-scale hydrocarbon fragments (thickness ≈ 0.5-2nm, C / O ratio <90%) still remain after the support layer is pyrolyzed. These fragments produce amorphous carbon diffraction rings (interplanar spacing d = 0.34nm) under electron beam irradiation, seriously interfering with the identification of sample lattice fringes and thus affecting subsequent analysis results. Experiments have shown that residues can degrade TEM resolution from the theoretical value of 0.1nm to >0.25nm. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to transfer a single-layer graphene containing a metal substrate prepared by the existing chemical vapor deposition method to a microgrid suitable for a transmission electron microscope, thereby obtaining an ultra-clean and large-area graphene backing, which is beneficial to improving the imaging contrast of light elements, small organic molecules, and single-atom clusters.
[0005] This invention provides a method for preparing atomically clean single-layer graphene transmission electron microscopy (TEM) grids. This method aims to overcome the contamination and defects that plague existing graphene transfer processes, ensuring the quality and performance of graphene for high-precision microscopy characterization. This method enables the transfer of high-quality single-layer graphene and is suitable for large-scale preparation and analysis, particularly in TEM observations.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions.
[0007] A method for preparing an atomically clean single-layer graphene transmission electron microscope (TEM) grid, comprising the following steps:
[0008] (1) growing a single layer of graphene on a metal substrate by chemical vapor deposition (CVD) to obtain a graphene / metal substrate;
[0009] (2) using an ozone-ultraviolet combined treatment method to remove residual organic matter on the surface of the graphene / metal substrate to obtain a graphene / metal substrate with the organic matter removed;
[0010] (3) using acetone to remove PMMA organic residues on the surface of the graphene / metal substrate from which organic matter has been removed to obtain a graphene / metal substrate from which PMMA has been removed;
[0011] (4) using a glass sheet to flatten the graphene / metal substrate from which PMMA has been removed;
[0012] (5) dripping an adhesive on the surface of the graphene layer of the graphene / metal substrate from which PMMA has been removed, and placing the front surface of the TEM micro-grid toward the graphene to bond the TEM micro-grid to the graphene to form a structural layer of the TEM micro-grid / graphene / metal substrate;
[0013] (6) placing the TEM micro-grid / graphene / metal substrate structure layer with the metal substrate facing downward on an oxidizing etching solution, and floatingly etching the metal substrate until the metal substrate is completely dissolved to obtain the TEM micro-grid / graphene; the oxidizing etching solution is an aqueous solution of one of sodium persulfate, potassium persulfate, ammonium persulfate or citric acid, the concentration of the aqueous solution of one of sodium persulfate, potassium persulfate, ammonium persulfate or citric acid is in the range of 8-10wt%, and the pH value of the oxidizing etching solution is adjusted to 1-4;
[0014] (7) cleaning and drying the TEM micro-grating / graphene to obtain clean TEM micro-grating / graphene;
[0015] (8) The cleaned TEM micro-grating / graphene is placed in a vacuum environment, and the residual binder and impurities on the TEM micro-grating / graphene are removed by three-stage step-by-step temperature-raising pyrolysis: the vacuum environment is 25°C before heating; in the first stage under vacuum conditions, the temperature is raised to 50-120°C at a rate of 15-20°C / min and then kept warm for 1 hour; in the second stage, the temperature is raised to 120-170°C at a rate of 5-10°C / min and kept warm for 1 hour; in the third stage, the temperature is raised to 170-180°C and kept warm for 5 hours.
[0016] Preferably, the method for removing the PMMA organic residue on the surface of the graphene / metal substrate of organic matter in step (3) is: weighing 99.5% pure acetone, adding it together with the graphene / metal substrate to a culture dish rinsed three times with deionized water, and placing the culture dish in a vacuum drying oven preheated to 56° C. for 10-20 minutes; repeating the above process of weighing acetone and graphene / metal substrate, adding it to the culture dish, and placing it in the vacuum drying oven for heating three times.
[0017] Preferably, the glass sheet in step (4) is washed three times with deionized water before the PMMA-removed graphene / metal substrate is flattened to generate a 0.3-0.5 cm 2 The flat area is large enough to cover the entire microgrid area.
[0018] Preferably, the adhesive in step (5) is isopropyl alcohol with a purity of 99.99%, and the bonding time is 2 hours.
[0019] Preferably, the cleaning in step (7) includes sequentially using deionized water and ethanol for ultrasonic-assisted rinsing of the TEM microgate / graphene, with each solvent rinsing 2-5 times and an ultrasonic power of 50-200W, and then vacuum drying the TEM microgate / graphene at a vacuum drying temperature of 50°C.
[0020] Preferably, the TEM microgrid in step (5) is a gold mesh or nickel mesh microgrid support film with an aperture of 2.5-10 μm and a carbon film thickness of 15-30 nm.
[0021] Preferably, the etching in step (6) causes the copper surface of the metal substrate to contact the etching solution, forming a structure of etching solution / metal substrate / graphene / TEM micro-gate.
[0022] Preferably, the vacuum condition in step (8) is to heat the container by placing a heating rod in a dry vacuum storage container, and the vacuum degree is 10 -6 Pa.
[0023] Preferably, the chemical vapor deposition (CVD) method in step (1) comprises the following specific steps:
[0024] The untreated metal substrate was ultrasonically cleaned in 99.99% pure isopropyl alcohol, anhydrous ethanol, and deionized water for approximately 10 minutes, respectively. The sonicated metal substrate was then placed in a 10% hydrochloric acid solution for 2 minutes, rinsed with deionized water, and dried with nitrogen. The substrate was then electrochemically polished in a polishing solution composed of 66.5 wt% phosphoric acid, 25 wt% sulfuric acid, 1 wt% hydrochloric acid, 4 wt% polyethylene glycol, 3 wt% glycerol, and 0.5 wt% tributyl phosphate for 12 minutes at 8 V.
[0025] The metal substrate is then immersed in 10% dilute hydrochloric acid (HCl) to remove residual oxides, followed by rinsing with deionized water and drying. The copper foil is then placed in a H2 / Ar mixture with a H2 ratio of 5-20% and heated to 1000-1060°C for 10-30 minutes. A mixed gas of CH4, H2, and Ar is then introduced, wherein the mass ratio of the mixed gas is CH4:H2:Ar=1:20:100, the pressure is 1-100 Pa, the temperature is 1000-1060°C, and the growth time is 20-40 minutes. After completion, the introduction of the mixed gas is stopped and the temperature is rapidly lowered at a rate greater than 50°C / s to inhibit the rearrangement of carbon atoms to form a multilayer structure.
[0026] Finally, polymethyl methacrylate (PMMA) is coated on the grown graphene / metal substrate for complete transfer.
[0027] The metal substrate is copper foil.
[0028] Preferably, the ozone-ultraviolet combined treatment method in step (2) is carried out as follows:
[0029] a) First, cut the grown graphene / metal substrate into 1×1 cm 2 Make sure the surface is clean and free of scratches or contaminants; then blow dry with nitrogen and place in a desiccator for later use;
[0030] b) The graphene / metal substrate is then secured to a bracket within a quartz chamber of a UV-ozone cleaning machine, and a UV light source with a wavelength of 185 nm is directed directly toward the sample surface; oxygen is introduced into the quartz chamber of the UV-ozone cleaning machine at a flow rate of 0.1–1 L / min, with the oxygen flow rate controlled by a mass flow meter to maintain a theoretical ozone concentration of 20–100 ppm;
[0031] c) irradiating the graphene / metal substrate with a UV light source having a wavelength of 254 nm for a time period of 0–30 minutes;
[0032] d) Finally, the UV light source was turned off, the ozone supply was stopped, and the quartz chamber of the UV-ozone cleaning machine was purged with nitrogen for 10 minutes to remove residual ozone, and the graphene / metal substrate was removed.
[0033] The method of the present invention can effectively transfer single-layer graphene to TEM micro-grid without loss, ensuring that the structure and performance of graphene remain unchanged, while greatly improving the TEM imaging resolution, achieving (Figure 4(b)), compared with the conventional method (Figure 2(c)) shows significant improvements. This method uses an adhesive to bond the graphene and TEM microgrid, avoiding the structural damage common in traditional transfer methods. Finally, a three-step heating process is used in a vacuum to pyrolyze and remove residual adhesive and impurities from the TEM microgrid / graphene, avoiding the contamination issues associated with traditional transfer methods and making it suitable for high-resolution electron microscopy imaging. This method is not only suitable for the transfer of single-layer graphene but also provides a viable technical path for the transfer of other two-dimensional materials, promising broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The present invention is a flow chart of a method for preparing an atomic-level clean single-layer graphene transmission electron microscope grid.
[0035] Figure 2a This is a low-magnification electron microscope image of a single-layer graphene transmission electron microscope grid prepared by traditional methods.
[0036] Figure 2b yes Figure 2a A magnified image of the white box area.
[0037] Figure 2c yes Figure 2b The Fourier transform image of .
[0038] Figure 3a This is a low-magnification electron microscope image of the atomic-level clean single-layer graphene transmission electron microscope grid prepared by the present invention.
[0039] Figure 3b yes Figure 3a Electron beam diffraction information diagram of the area.
[0040] Figure 4a This is a TEM image of a single-layer graphene under a transmission electron microscope equipped with the transmission electron microscope grid prepared in Example 3.
[0041] Figure 4b yes Figure 4a The Fourier transform image of .
[0042] Figure 4c for Figure 4a A magnified image of the white box area. Specific implementation methods
[0043] The present invention will be described in detail below with reference to the accompanying drawings and specific examples, but they should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the following examples are conventional means well known to those skilled in the art, and the materials, reagents, etc. used in the following examples, unless otherwise specified, can be obtained from commercial sources.
[0044] The method for preparing atomically clean single-layer graphene TEM grid will be described in detail below with reference to the accompanying drawings.
[0045] Example 1
[0046] In this example, a single-layer graphene was grown on a copper substrate using chemical vapor deposition (CVD) and a gold mesh micro-grid support film (5 μm pore size, 15 nm carbon film thickness) was used for transfer.
[0047] (1) The specific steps of growing single-layer graphene on a copper substrate using chemical vapor deposition (CVD) are as follows: the untreated copper foil is ultrasonically cleaned in 99.99% pure isopropyl alcohol, anhydrous ethanol, and deionized water for about 10 minutes. The sonicated copper foil is then placed in a 10% hydrochloric acid solution for 2 minutes, then rinsed with deionized water and blown dry with nitrogen. Electrochemical polishing is then performed, with the electropolishing time set to 12 minutes and the voltage set to 8V. The polishing solution consists of 66.5% phosphoric acid, 25% sulfuric acid, 1% hydrochloric acid, 4% polyethylene glycol, 3% glycerol, and 0.5% tributyl phosphate. The copper foil was then immersed in 10% dilute hydrochloric acid (HCl) to remove any residual oxides, then rinsed with deionized water and dried. The copper foil was then heated to 1060°C in a 5% H2 / Ar mixture for 10 minutes. A mixture of CH4, H2, and Ar was then introduced at a ratio of 1:20:100, a pressure of 100 Pa, and a temperature of 1060°C for 20 minutes. The addition of the mixed gas was then stopped and the temperature was rapidly cooled at a rate of 55°C / s to prevent the carbon atoms from rearranging and forming a multilayer structure. Finally, the grown graphene / metal substrate was coated with polymethyl methacrylate (PMMA) to facilitate complete transfer.
[0048] (2) Using ozone-ultraviolet combined treatment method to preliminarily remove the organic matter remaining on the graphene surface. The specific steps are as follows: First, cut the grown graphene / metal substrate into 1×1 cm 2The sample was fixed on a bracket in the quartz chamber of the UV-ozone cleaning machine, and a UV light source with a wavelength of 185nm was directed directly at the sample surface. Oxygen was introduced into the chamber at a flow rate of 0.1L / min, and the oxygen flow rate was controlled by a mass flow meter to generate ozone with a set concentration stable at 20-100ppm. The 254nm UV light source was then turned on for 0 minutes. Finally, the UV light source was turned off, the ozone supply was stopped, and the chamber was purged with nitrogen for 10 minutes to remove any residual ozone. The graphene / metal substrate was then removed.
[0049] (3) Using acetone to deeply remove PMMA organic residues on the graphene surface, the specific steps are as follows: weigh 20 ml of acetone with a purity of 99.5%, place it in a cleaning dish together with the graphene / metal substrate, and place it in a vacuum drying oven preheated to 56°C for 10 minutes, repeating three times;
[0050] (4) Using quartz glass (area 2*5cm 2 ) Flatten the graphene / metal substrate to ensure close contact between the two. Rinse the glass sheet with deionized water three times.
[0051] (5) Add isopropyl alcohol (99.99% purity, 0.8 mL) as an adhesive to the graphene surface and align the TEM microgrid to the graphene to form a TEM microgrid / graphene / metal substrate structure. During this process, ensure that the front of the TEM microgrid faces the graphene side to avoid any structural damage. The bonding time is 2 hours.
[0052] (6) Using an oxidizing etchant, ammonium persulfate solution (8 wt %), with a pH adjusted to 1.5, the metal substrate is etched to form a structure layer of TEM micro-grid / graphene / metal substrate / etchant, ensuring that the copper surface of the metal substrate is in direct contact with the etchant without bubbles, and completely dissolving the metal substrate;
[0053] (7) Perform multi-stage cleaning on the TEM microgrid / graphene structure, using deionized water and ethanol for ultrasonic rinsing in sequence, rinsing twice with each solvent, with an ultrasonic power of 200 W, and vacuum drying at a temperature of 50°C;
[0054] (8) The TEM microgrid / graphene was placed in a vacuum environment and the residual binder and impurities on the TEM microgrid / graphene were removed by a three-stage step-by-step heating pyrolysis: the environment before heating was 25°C. In the first stage, the temperature was increased to 50°C at a rate of 15°C / min and then kept at this temperature for 1 hour; in the second stage, the temperature was increased to 120°C at a rate of 5°C / min and kept at this temperature for 1 hour; in the third stage, the temperature was increased to 170°C at a rate of 5°C / min and kept at this temperature for 5 hours. After heating, the sample was cooled to room temperature in a vacuum environment and then tested.
[0055] Example 2
[0056] In this example, a single-layer graphene was grown on a copper substrate using CVD, and a gold mesh micro-grid support film (5 μm pore size, 15 nm carbon film thickness) was used for transfer.
[0057] (1) The specific steps of growing single-layer graphene on a copper substrate using chemical vapor deposition (CVD) are as follows: the untreated copper foil is ultrasonically cleaned in 99.99% pure isopropyl alcohol, anhydrous ethanol, and deionized water for about 10 minutes. The sonicated copper foil is then placed in a 10% hydrochloric acid solution for 2 minutes, then rinsed with deionized water and blown dry with nitrogen. Electrochemical polishing is then performed, with the electropolishing time set to 12 minutes and the voltage set to 8V. The polishing solution consists of 66.5% phosphoric acid, 25% sulfuric acid, 1% hydrochloric acid, 4% polyethylene glycol, 3% glycerol, and 0.5% tributyl phosphate. The copper foil was then immersed in 10% dilute hydrochloric acid (HCl) to remove any residual oxides, then rinsed with deionized water and dried. The copper foil was then placed in a 10% H2 / Ar mixture and heated to 1000°C for 20 minutes. A mixture of CH4, H2, and Ar was then introduced, with a ratio of CH4:H2:Ar = 1:20:100, at a pressure of 10 Pa and a temperature of 1000°C for 30 minutes. After this, the gas mixture was stopped and the temperature was rapidly cooled at 60°C / s to prevent the carbon atoms from rearranging and forming a multilayer structure. Finally, the grown graphene / metal substrate was coated with polymethyl methacrylate (PMMA) to facilitate complete transfer.
[0058] (2) Using ozone-ultraviolet combined treatment method to preliminarily remove the organic matter remaining on the graphene surface. The specific steps are as follows: First, cut the grown graphene / metal substrate into 1×1 cm 2The size of the sample is determined by the size of the sample, ensuring that the surface is clean and free of scratches or contaminants. It is then blown dry with nitrogen and placed in a desiccator for later use. The sample is then fixed on a bracket in the quartz chamber of the UV-ozone cleaning machine, and a UV light source with a wavelength of 185nm is directed directly at the sample surface. Oxygen is introduced into the chamber at a flow rate of 0.5L / min, and the oxygen flow rate is controlled by a mass flow meter to generate ozone with a set concentration stable at 20-100ppm. The 254nm UV light source is then turned on for 15 minutes. Finally, the UV light source is turned off, the ozone supply is stopped, and the chamber is purged with nitrogen for 10 minutes to remove residual ozone. The graphene / metal substrate can then be removed.
[0059] (3) Use acetone to deeply remove PMMA organic residues on the graphene surface. The specific steps are as follows: weigh 20 ml of acetone, put it into a cleaning dish together with the graphene copper sheet, and place it in a vacuum drying oven preheated to 56 ° C for 15 minutes, repeating 3 times;
[0060] (4) Using quartz glass (area 2*5cm 2 ) Flatten the graphene and metal substrate to ensure close contact between them. The glass sheet is cleaned with deionized water three times.
[0061] (5) Add isopropyl alcohol (99.99% purity, 0.8 mL) as an adhesive to the graphene surface and align the TEM microgrid to the graphene to form a TEM microgrid / graphene / metal substrate structure. During this process, ensure that the front of the TEM microgrid faces the graphene side to avoid any structural damage. The bonding time is 2 hours.
[0062] (6) The oxidizing etching solution uses a potassium persulfate solution (concentration of 8 wt%), with 0.05 M citric acid, and the pH value is adjusted to 2 to etch the metal substrate to form a structure layer of TEM micro-grid / graphene / metal substrate / etching solution, ensuring that the copper surface of the metal substrate is in direct contact with the etching solution without bubbles, and completely dissolving the metal substrate;
[0063] (7) Perform multi-stage cleaning on the TEM microgrid / graphene structure, using deionized water and ethanol for ultrasonic rinsing in sequence, with each solvent rinsed 4 times, the ultrasonic power was 140W, and vacuum drying was performed at a temperature of 50°C;
[0064] (8) The TEM microgrid / graphene was placed in a vacuum environment and the residual binder and impurities on the TEM microgrid / graphene were removed by a three-stage step-by-step pyrolysis: the environment was 25°C before heating; in the first stage, the temperature was increased to 110°C at a rate of 16°C / min and then kept at this temperature for 1 hour; in the second stage, the temperature was increased to 150°C at a rate of 7°C / min and kept at this temperature for 1 hour; in the third stage, the temperature was increased to 180°C at a rate of 5°C / min and kept at this temperature for 5 hours. After heating, the sample was cooled to room temperature in a vacuum environment and then tested.
[0065] Example 3
[0066] In this example, a single-layer graphene was grown on a copper substrate using chemical vapor deposition (CVD) and transferred using a nickel mesh micro-grid support film (5 μm pore size, 15 nm carbon film thickness);
[0067] (1) The specific steps of growing a single layer of graphene on a copper substrate using chemical vapor deposition (CVD) are as follows: The untreated copper foil is ultrasonically washed in 99.99% pure isopropyl alcohol, anhydrous ethanol and deionized water for about 10 minutes. The sonicated copper foil is then placed in a 10% hydrochloric acid solution for 2 minutes, then rinsed with deionized water and blown dry with nitrogen. Electrochemical polishing is then performed, with the electropolishing time set to 12 minutes and the voltage set to 8V. The polishing solution consists of 66.5wt% phosphoric acid, 25wt% sulfuric acid, 1wt% hydrochloric acid, 4wt% polyethylene glycol, 3wt% glycerol and 0.5wt% tributyl phosphate. The copper foil was then immersed in 10% dilute hydrochloric acid (HCl) to remove any residual oxides, then rinsed with deionized water and dried. The copper foil was then placed in a 20% H2 / Ar mixture and heated to 1050°C for 30 minutes. A mixture of CH4, H2, and Ar was then introduced, with a ratio of CH4:H2:Ar of 1:20:100, at a pressure of 1 Pa and a temperature of 1050°C for 40 minutes. After this, the gas mixture was stopped and the temperature was rapidly cooled at a rate of 55°C / s to prevent the carbon atoms from rearranging and forming a multilayer structure. Finally, the grown graphene / metal substrate was coated with polymethyl methacrylate (PMMA) to facilitate complete transfer.
[0068] (2) Using ozone-ultraviolet combined treatment method to preliminarily remove the organic matter remaining on the graphene surface. The specific steps are as follows: First, cut the grown graphene / metal substrate into 1×1 cm 2The size of the sample is determined by the size of the sample, ensuring that the surface is clean and free of scratches or contaminants. It is then blown dry with nitrogen and placed in a desiccator for later use. The sample is then fixed on a bracket in the quartz chamber of the UV-ozone cleaning machine, and a UV light source with a wavelength of 185nm is directed directly at the sample surface. Oxygen is introduced into the chamber at a flow rate of 1L / min, and the oxygen flow rate is controlled by a mass flow meter to generate ozone with a set concentration stable at 20-100ppm. The 254nm UV light source is then turned on for 30 minutes. Finally, the UV light source is turned off, the ozone supply is stopped, and the chamber is purged with nitrogen for 10 minutes to remove residual ozone. The graphene / metal substrate can then be removed.
[0069] (3) Use acetone to deeply remove PMMA organic residues on the graphene surface. The specific steps are as follows: weigh 20 ml of acetone, put it into a cleaning dish together with the graphene copper sheet, and place it in a vacuum drying oven preheated to 56 ° C for 20 minutes, repeating 3 times;
[0070] (4) Using quartz glass (area 2*5cm 2 ) Flatten the graphene and metal substrate to ensure close contact between them. The glass sheet is cleaned with deionized water three times.
[0071] (5) Add isopropyl alcohol (99.99% purity, 0.8 mL) as an adhesive to the graphene surface and align the TEM microgrid to the graphene to form a TEM microgrid / graphene / metal substrate structure. During this process, ensure that the front of the TEM microgrid faces the graphene side to avoid any structural damage. The bonding time is 2 hours.
[0072] (6) Using a sodium persulfate solution (8 wt %) as the oxidizing etching solution, the pH value is adjusted to 1.5 to etch the metal substrate, forming a structure layer of TEM micro-grid / graphene / metal substrate / etching solution, ensuring that the copper surface of the metal substrate is in direct contact with the etching solution without bubbles, and completely dissolving the metal substrate;
[0073] (7) Perform multi-stage cleaning on the TEM microgrid / graphene structure, using deionized water and ethanol for ultrasonic rinsing in sequence, with each solvent rinsed 5 times, the ultrasonic power is 50W, and vacuum drying is carried out at a temperature of 50°C;
[0074] (8) The TEM microgrid / graphene was placed in a vacuum environment and the residual binder and impurities on the TEM microgrid / graphene were removed by a three-stage step-by-step pyrolysis: the environment before heating was 25°C. In the first stage, the temperature was increased to 120°C at a rate of 20°C / min and then kept at this temperature for 1 hour; in the second stage, the temperature was increased to 170°C at a rate of 10°C / min and kept at this temperature for 1 hour; in the third stage, the temperature was increased to 180°C at a rate of 5°C / min and kept at this temperature for 5 hours. After heating, the sample was cooled to room temperature in a vacuum environment and then tested.
[0075] The grid prepared in this example was placed into a blank TEM sample holder for characterization. The low-magnification electron microscope image obtained is as follows: Figure 3a As shown, the TEM parameters are set to 300kV. During the imaging process, by adjusting the defocus of the objective lens to -10nm and combining the spherical aberration correction system (spherical aberration coefficient Cs = 975nm), the imaging resolution reaches
[0076] Comparative Example
[0077] In this comparative example, a single layer of graphene was grown on a copper substrate using chemical vapor deposition (CVD) and transferred using a nickel mesh micro-grid support film (pore size 5 μm, carbon film thickness 15 nm);
[0078] (1) The specific steps of growing single-layer graphene on a copper substrate using chemical vapor deposition (CVD) are as follows: the untreated copper foil is ultrasonically cleaned in 99.99% pure isopropyl alcohol, anhydrous ethanol, and deionized water for about 10 minutes. The sonicated copper foil is then placed in a 10% hydrochloric acid solution for 2 minutes, then rinsed with deionized water and blown dry with nitrogen. Electrochemical polishing is then performed, with the electropolishing time set to 12 minutes and the voltage set to 8V. The polishing solution consists of 66.5% phosphoric acid, 25% sulfuric acid, 1% hydrochloric acid, 4% polyethylene glycol, 3% glycerol, and 0.5% tributyl phosphate. The copper foil was then immersed in 10% dilute hydrochloric acid (HCl) to remove residual oxides, then rinsed with deionized water and dried. The copper foil was then placed in a 20% H2 / Ar mixture and heated to 1050°C for 30 minutes. A mixture of CH4, H2, and Ar was then introduced, with a ratio of CH4:H2:Ar = 1:20:100, at a pressure of 1 Pa and a temperature of 1050°C for 40 minutes. After this, the gas mixture was stopped and the temperature was rapidly cooled at a rate exceeding 50°C / s to prevent the carbon atoms from rearranging and forming a multilayer structure. Finally, the grown graphene / metal substrate was coated with polymethyl methacrylate (PMMA) to facilitate complete transfer.
[0079] (2) Using ozone-ultraviolet combined treatment method to preliminarily remove the organic matter remaining on the graphene surface. The specific steps are as follows: First, cut the grown graphene / metal substrate into 1×1 cm 2 The size of the sample is determined by the size of the sample, ensuring that the surface is clean and free of scratches or contaminants. It is then blown dry with nitrogen and placed in a desiccator for later use. The sample is then fixed on a bracket in the quartz chamber of the UV-ozone cleaning machine, and a UV light source with a wavelength of 185nm is directed directly at the sample surface. Oxygen is introduced into the chamber at a flow rate of 1L / min, and the oxygen flow rate is controlled by a mass flow meter to generate ozone with a set concentration stable at 20-100ppm. The 254nm UV light source is then turned on for 30 minutes. Finally, the UV light source is turned off, the ozone supply is stopped, and the chamber is purged with nitrogen for 10 minutes to remove residual ozone. The graphene / metal substrate can then be removed.
[0080] (3) Use acetone to deeply remove PMMA organic residues on the graphene surface. The specific steps are as follows: weigh 20 ml of acetone, put it into a cleaning dish together with the graphene copper sheet, and place it in a vacuum drying oven preheated to 56 ° C for 20 minutes, repeating 3 times;
[0081] (4) Using quartz glass (area 2*5cm 2 ) Flatten the graphene and metal substrate to ensure close contact between them. The glass sheet is cleaned with deionized water three times.
[0082] (5) Add isopropyl alcohol (99.99% purity, 0.8 mL) as an adhesive to the graphene surface and align the TEM microgrid to the graphene to form a TEM microgrid / graphene / metal substrate structure. During this process, ensure that the front of the TEM microgrid faces the graphene side to avoid any structural damage. The bonding time is 2 hours.
[0083] (6) Using a sodium persulfate solution (8 wt %) as the oxidizing etching solution, the pH value is adjusted to 1.5 to etch the metal substrate, forming a structure layer of TEM micro-grid / graphene / metal substrate / etching solution, ensuring that the copper surface of the metal substrate is in direct contact with the etching solution without bubbles, and completely dissolving the metal substrate;
[0084] (7) Perform multi-stage cleaning on the TEM microgrid / graphene structure, using deionized water and ethanol for ultrasonic rinsing in sequence, with each solvent rinsed 5 times, the ultrasonic power is 50W, and vacuum drying is carried out at a temperature of 50°C;
[0085] (8) Place the TEM microgrid / graphene in a vacuum environment and remove the residual binder and impurities on the TEM microgrid / graphene by heating and pyrolysis: the heating rate is 20°C / min, the temperature is raised to 180°C and then kept at this temperature for 7 hours. After heating, cool to room temperature in a vacuum environment and then test.
[0086] The grid prepared in this comparative example was placed into a blank TEM sample holder for characterization and the low-magnification electron microscope image obtained was as follows: Figure 2a As shown, the TEM parameters are set to 300kV. During the imaging process, by adjusting the defocus of the objective lens to -10nm and combining the spherical aberration correction system (spherical aberration coefficient Cs = 975nm), the imaging resolution reaches
[0087] Analytical characterization
[0088] After testing, it was found that the transfer methods described in Examples 1-3 can obtain relatively good single-layer clean graphene for transmission electron microscopy observation. Here, the single-layer clean graphene grids prepared in Example 3 and the comparative example were used for transmission electron microscopy (TEM) observation.
[0089] The single-layer clean graphene grids prepared in Example 3 and the comparative example were characterized using a high-resolution transmission electron microscope (HRTEM, model Themis-ETEM) at an accelerating voltage of 300 kV. During the characterization process, the objective lens defocus was adjusted to -10 nm and a spherical aberration correction system (spherical aberration coefficient Cs = 975 nm) was used. The comparative example TEM low-magnification characterization results are shown in Figure 2. Figure 2a As shown, the TEM low-magnification characterization results of Example 3 are as follows Figure 2a Figure 3a shown; combined Figure 2c and Figure 3b The diffraction information of Example 3 can prove that the characterization clarity of the results is higher than that of the comparative example. Figure 4a 30um can be directly observed 2 The above single-layer clean graphene structure is composed of Figure 4a After Fourier transform, we get Figure 4b Resolution up to From Figure 4a Local magnification Figure 4c The clean six-membered ring structure of graphene can be clearly observed. This method uses an adhesive to bond the graphene and TEM microgrid, avoiding the structural damage common in traditional transfer methods. Finally, a three-step heating method is used in a vacuum to pyrolyze and remove the residual adhesive and impurities on the TEM microgrid / graphene, avoiding the contamination problems of traditional transfer methods and making it suitable for high-resolution electron microscopy imaging.
[0090] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0091] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if such changes and modifications fall within the scope of the claims and their equivalents, the present invention is intended to include such changes and modifications.
Claims
1. A method for preparing an atomically clean single-layer graphene transmission electron microscope grid, comprising the following steps: (1) growing a single layer of graphene on a metal substrate by chemical vapor deposition (CVD) to obtain a graphene / metal substrate; (2) using an ozone-ultraviolet combined treatment method to remove residual organic matter on the surface of the graphene / metal substrate to obtain a graphene / metal substrate with the organic matter removed; (3) using acetone to remove PMMA organic residues on the surface of the graphene / metal substrate from which organic matter has been removed to obtain a graphene / metal substrate from which PMMA has been removed; (4) using a glass sheet to flatten the graphene / metal substrate from which PMMA has been removed; (5) dripping an adhesive on the surface of the graphene layer of the graphene / metal substrate from which PMMA has been removed, and placing the front surface of the TEM micro-grid toward the graphene to bond the TEM micro-grid to the graphene to form a structural layer of the TEM micro-grid / graphene / metal substrate; (6) placing the TEM micro-grid / graphene / metal substrate structure layer with the metal substrate facing downward on an oxidizing etching solution, and floatingly etching the metal substrate until the metal substrate is completely dissolved to obtain the TEM micro-grid / graphene; the oxidizing etching solution is an aqueous solution of one of sodium persulfate, potassium persulfate, ammonium persulfate or citric acid, the concentration of the aqueous solution of one of sodium persulfate, potassium persulfate, ammonium persulfate or citric acid is in the range of 8-10wt%, and the pH value of the oxidizing etching solution is adjusted to 1-4; (7) cleaning and drying the TEM micro-grating / graphene to obtain clean TEM micro-grating / graphene; (8) The cleaned TEM micro-grating / graphene is placed in a vacuum environment, and the residual binder and impurities on the TEM micro-grating / graphene are removed by three-stage step-by-step temperature-raising pyrolysis: the vacuum environment is 25°C before heating; in the first stage under vacuum conditions, the temperature is raised to 50-120°C at a rate of 15-20°C / min and then kept warm for 1 hour; in the second stage, the temperature is raised to 120-170°C at a rate of 5-10°C / min and kept warm for 1 hour; in the third stage, the temperature is raised to 170-180°C and kept warm for 5 hours.
2. The method according to claim 1, wherein: The method for removing the PMMA organic residue on the surface of the graphene / metal substrate of the organic matter in step (3) is as follows: weighing 99.5% pure acetone, adding it together with the graphene / metal substrate to a culture dish rinsed three times with deionized water, and placing the culture dish in a vacuum drying oven preheated to 56° C. for 10-20 minutes; the process of adding the above-mentioned acetone and graphene / metal substrate to the culture dish and heating it in the vacuum drying oven is repeated three times.
3. The method according to claim 1, wherein: Step (4) The glass sheet is washed 3 times with deionized water before the PMMA-removed graphene / metal substrate is flattened to generate a 0.3-0.5 cm 2 flat area.
4. The method according to claim 1, wherein: The adhesive in step (5) is isopropyl alcohol with a purity of 99.99%, and the bonding time is 2 hours.
5. The method according to claim 1, wherein: The cleaning in step (7) includes sequentially using deionized water and ethanol for ultrasonic-assisted rinsing of the TEM microgrid / graphene, with each solvent rinsing 2-5 times and an ultrasonic power of 50-200W, and then vacuum drying the TEM microgrid / graphene at a vacuum drying temperature of 50°C.
6. The method according to claim 1, wherein: The TEM microgrid in step (5) is a gold mesh or nickel mesh microgrid support film with an aperture of 2.5-10 μm and a carbon film thickness of 15-30 nm.
7. The method according to claim 1, wherein: The etching in step (6) causes the copper surface of the metal substrate to contact the etching solution, forming a structure of etching solution / metal substrate / graphene / TEM micro-gate.
8. The method according to claim 1, wherein: The vacuum condition in step (8) is to heat the container by heating the heating rod in a dry vacuum storage container, and the vacuum degree is 10 -6 Pa.
9. The method according to claim 1, wherein: The specific steps of the chemical vapor deposition (CVD) method in step (1) are as follows: The untreated metal substrate was ultrasonically cleaned in 99.99% pure isopropyl alcohol, anhydrous ethanol, and deionized water for approximately 10 minutes, respectively. The sonicated metal substrate was then placed in a 10% hydrochloric acid solution for 2 minutes, rinsed with deionized water, and dried with nitrogen. The substrate was then electrochemically polished in a polishing solution composed of 66.5 wt% phosphoric acid, 25 wt% sulfuric acid, 1 wt% hydrochloric acid, 4 wt% polyethylene glycol, 3 wt% glycerol, and 0.5 wt% tributyl phosphate for 12 minutes at 8 V. The metal substrate was then immersed in 10% dilute hydrochloric acid HCl to remove residual oxides, followed by rinsing with deionized water and drying; The copper foil is then placed in a H2 / Ar mixture with a H2 ratio of 5-20% and heated to 1000-1060°C for 10-30 minutes; then a mixed gas of CH4, H2, and Ar is introduced, wherein the mass ratio of the mixed gas is: CH4:H2:Ar=1:20:100, the pressure is 1-100 Pa, the temperature is 1000-1060°C, and the growth time is 20-40 minutes; after the end, the mixed gas is stopped and the temperature is rapidly cooled at a rate higher than 50°C / s; Finally, polymethyl methacrylate (PMMA) is coated on the grown graphene / metal substrate for complete transfer. The metal substrate is copper foil.
10. The method according to claim 1, wherein: The ozone-ultraviolet combined treatment method in step (2) is carried out as follows: a) First, cut the grown graphene / metal substrate into 1×1 cm 2 Make sure the surface is clean and free of scratches or contaminants; then blow dry with nitrogen and place in a desiccator for later use; b) Then the graphene / metal substrate is fixed on a bracket in the quartz chamber of the UV-ozone cleaning machine, A UV light source with a wavelength of 185 nm was directed toward the sample surface. Oxygen at a flow rate of 0.1–1 L / min was introduced into the quartz chamber of the UV ozone cleaning machine. The oxygen flow rate was controlled by a mass flow meter to maintain the theoretical concentration of generated ozone at 20–100 ppm. c) irradiating the graphene / metal substrate with a UV light source having a wavelength of 254 nm for a time period of 0–30 minutes; d) Finally, the UV light source was turned off, the ozone supply was stopped, and the quartz chamber of the UV-ozone cleaning machine was purged with nitrogen for 10 minutes to remove residual ozone, and the graphene / metal substrate was removed.